PELATIHAN OLAHAN PISANG MENJADI DODOL PISANG DI DESA MAOS LOR KECAMATAN MAOS KABUPATEN CILACAP - Susanti Susanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Maos Lor Village, is one of the villages that has considerable agricultural potential and is one of the centers for banana production. However, the added value of banana cultivation in the village is not yet optimal. The selling price of bananas given is still quite low so that it has an impact on the level of economic development of the community which is still low when compared to the potential of the area owned. The objectives of this community service are to: 1) Increase knowledge in processing bananas into banana Dodol through training for community groups in the Maos Lor Village environment and 2) Improve community skills in increasing the added value of the Banana Dodol processed business. The activity was carried out in March-July (4 months) with several activities including socialization, training on making Calcium Dodol and post-production assistance. The results of this activity include the formation of a small business group of Banana Dodol